Perkembangan Psikologi Pendidikan Islam dalam Perspektif Filsafat Ilmu dan Sejarah Pendidikan Islam - Afiffudin, Muhamad; Tarsono, Tarsono; Hermawan, Acep Heris; Haryanti, Erni; Mustakin, Akin; Mungkassifurahman, Mungkassifurahman (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Study of the development of Islamic Educational Psychology understands how Islamic principles interact with modern educational theory and practice. In terms of the philosophy of science, Islamic Educational Psychology is not only considered a branch of science oriented towards learning behaviour, but also a discipline that has a distinctive ontological, epistemological, and axiological foundation in accordance with Islamic values. This study aims to analyse development of Islamic Educational Psychology from the perspective of the philosophy of science and the history of Islamic education in order to understand how the integration of spiritual values, scientific rationality, and human educational needs is carried out within the framework of Islamic science. The method used is a literature review with a historical-philosophical approach, which examines classical and contemporary sources related to Islamic education and psychology. The results of the study show that Islamic Educational Psychology has undergone significant development from classical to contemporary times, with major contributions from Muslim thinkers such as Al-Ghazali, Ibn Sina, and Ibn Khaldun, who emphasised the balance between spiritual and intellectual aspects in the educational process. From a philosophical perspective, Islamic Educational Psychology seeks to develop an integrative scientific paradigm, combining empirical and spiritual dimensions in understanding human behaviour.Keywords – Philosophy, Psychology, Integration, Islamic Education.